Screening for Cardiac Magnetic Resonance Scar Features by 12‐Lead ECG, in Patients with Preserved Ejection Fraction. Issue 1 (January 2016) - Mewton, Nathan; Strauss, David G.; Rizzi, Patricia; Verrier, Richard L.; Liu, Chia Ying; Tereshchenko, Larisa G.; Nearing, Bruce; Volpe, Gustavo J.; Marchlinski, Francis E.; Moxley, John; Killian, Tony; Wu, Katherine C.; et al.
Abstract : Background: Increased QRS score and wide spatial QRS‐T angle are independent predictors of cardiovascular mortality in the general population . Our main objective was to assess whether a QRS score ≥5 and/or QRS‐T angle ≥105° enable screening of patients for myocardial scar features. Methods: Seventy‐seven patients of age ≤70 years with QRS score ≥5 and/or spatial QRS‐T angle ≥105° as well as left ventricular ejection fraction (LVEF) >35% were enrolled in the study. All participants underwent complete clinical examination, signal‐averaged ECG (SAECG), 30‐minute ambulatory ECG recording for T‐wave alternans (TWA), and late gadolinium enhancement cardiac magnetic resonance (LGE‐CMR). Relationship between QRS score, QRS‐T angle with scar presence and pattern, as well as gray zone, core, and total scar size by LGE‐CMR were assessed. Results: Myocardial scar was present in 41 (53%) patients, of whom 19 (46%) exhibited a typical ischemic pattern. QRS score but not QRS‐T angle was related to total scar size and gray zone size (R 2 = 0.12, P = 0.002; R 2 = 0.17; P ≤ 0.0001, respectively). Patients with QRS scores ≥6 had significantly greater myocardial scar and gray zone size, increased QRS duration and QRS‐T angle, a higher prevalence of late potentials (LPs) presence, increased LV end‐diastolic volume and decreased LVEF. There was a significant independent and positive association between TWA value and total scar (P = 0.001) and gray zone size (P = 0.01). Conclusion: Patients with preserved LVEF and myocardial scar by CMR also have electrocardiographic features that could be involved in ventricular arrhythmogenesis.